The effect of hydroalcoholic extract and essential oil of Heracleum persicum on lipid profile in cholesterol-fed rabbits - Valiollah Hajhashemi; Gholamreza Dashti; Salabali Saberi; Parvin Malekjamshidi (Mashhad University of Medical Sciences, 2014)
Objective: This study was designed to investigate the effect of hydroalcoholic extract and essential oil of Heracleum persicum (Apiaceae) on lipid profile of male hyperlipidemic rabbits. Materials and Methods: Thirty rabbits were randomly divided into six groups of five each. One group received normal diet and the other groups fed with a high cholesterol (2% W/W) diet for 7 weeks. Vehicle, hydroalcoholic extract (500 and 1000 mg/kg), essential oil (200 ml/kg), and lovastatin (5 mg/kg) were administered orally to animals and their effects on lipid profile were evaluated. Results: Essential oil of H. perscum significantly (p